Wednesday

July 30, 2014

July 30, 2014

Posted by **kota** on Friday, December 16, 2011 at 5:23pm.

A=-3(a=b-1/3c)

- Algebra -
**drwls**, Friday, December 16, 2011 at 7:11pmThere can be no = sign within parentheses. What did you really man to write?

Also: Is the c meant to be in the denominator with the last 3?

- Algebra -
**Steve**, Saturday, December 17, 2011 at 3:20pmSince + is shift=, I'll guess it's supposed to be

A = -3(a + b - 1/3 c)

-A/3 = a + b - 1/3 c

-(A/3 + a + b) = -c/3

c = A + 3a + 3b

**Related Questions**

Math - We have an important chemsitry test due and I want to make sure that I do...

Intermediate Algebra - Combine like terms: -3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x...

algebra - Solve the indicated variable: 1. Volume of a cone: solve for h: V=Ļir^...

Algebra - Solve for x: h=(k/4)(x-3L) Solve for B: v-6Bxk=7B Solve for S: z+(1/7)...

Algebra - Hi, how would I solve these 2 equations using algebra? It states in ...

Algebra 2 - Solve each system 3x+2y= -2 9x- y= -6 I know how to solve for x but ...

Algebra 2 - How do I solve these inequalities: e^3x>e^x-1 -6log (subscript of...

algebra - solve for the indicated variable: a. temperature formula solve for F: ...

Algebra - FIND THE GCF OF THE PRODUCT (3B+6)(2B-10) SOLVE... X^2=-6X x(x+6)= 0 x...

algebra - im trying to solve a literal equation, then solve the specific ...